THE ROLE OF TRUST, NETWORKS AND INSTITUTIONS ON THE PERFORMANCE OF VILLAGE-OWNED ENTERPRISES AND COMMUNITY ECONOMIC EMPOWERMENT IN VILLAGES - Nasfi, Nasfi; Sabri, Sabri; Febrina, Reni; Octaviani, Rizda (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Trust, networks, and institutions as local wisdom in villages are often overlooked, even though local wisdom is social capital that plays a role in bridging the performance of village-owned enterprises or BUMDes in empowering the village community's economy. The purpose of this study was to determine the influence of trust, networks, and institutions, as well as BUMDes performance on the economic empowerment of village communities. The Cluster Sampling technique was used to determine the sample and obtained a sample of 194 as well as being used as a research sample from 30 BUMDes spread across West Sumatra Province that had complete reports to the relevant agencies, then the questionnaire was distributed to supervisors, BUMDes directors, BUMDes employees, and BUMDes customer communities and the questionnaire was assessed using a circle scale. The data were analyzed using SPSS statistical software (version 25), then instrument testing consisting of validity and reliability testing using Smart-PLS software. The results of the study showed a direct positive effect of trust and network variables on BUMDes performance, and the influence of BUMDes performance on community economic empowerment. Institutions do not have a significant influence on BUMDes performance, but have a significant influence on community economic empowerment. The novelty of this research is to investigate the influence of social capital and BUMDes performance on community economic empowerment. The research implications expand the theory of social capital that positively influences the growth of BUMDes performance and has practical impacts for policy makers in increasing rural economic empowerment.